1998
DOI: 10.1074/jbc.273.30.19207
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of CDK Inhibitor p21Cip1/Waf1 by Caspases Is an Early Event during DNA Damage-induced Apoptosis

Abstract: Activation of the p53-mediated DNA damage response induces either G 1 cell cycle arrest or apoptosis. The G 1 cell cycle arrest is in part caused by the p53-dependent transcriptional activation of the CDK inhibitor, p21 Cip1/ Waf1. We report here that human p21 protein is rapidly induced but selectively cleaved during the apoptotic response to ␥-irradiation. Such an event occurred early, well before the morphological appearance of apoptosis. Ectopical expression of p53 in tumor cells alone could induce p21 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
112
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(129 citation statements)
references
References 31 publications
15
112
2
Order By: Relevance
“…A similar phenomenon has been reported in Saos-2 osteosarcoma cells (Tang et al, 1998). Nevertheless, increases in expression of p21 CIP1 over basal levels were most prominent in HMBA-treated cells, which also displayed evidence of a cross-reactive *17-kDa species, possibly representing a p21 CIP1 cleavage product (Gervais et al, 1998).…”
Section: Saha Induces Prb Dephosphorylation and Cleavage And Extensisupporting
confidence: 82%
“…A similar phenomenon has been reported in Saos-2 osteosarcoma cells (Tang et al, 1998). Nevertheless, increases in expression of p21 CIP1 over basal levels were most prominent in HMBA-treated cells, which also displayed evidence of a cross-reactive *17-kDa species, possibly representing a p21 CIP1 cleavage product (Gervais et al, 1998).…”
Section: Saha Induces Prb Dephosphorylation and Cleavage And Extensisupporting
confidence: 82%
“…As depicted in Figure 1a, Tera and A2780 cells revealed similar cisplatin-induced p53 protein accumulation, but only a marginal induction of p21 protein was observed in Tera cells in comparison to A2780 cells. p21 protein level can be regulated by proteasomal degradation or caspase-mediated cleavage (Gervais et al, 1998;Levkau et al, 1998;Zhang et al, 1999;Naujokat and Hoffmann, 2002;Xiang et al, 2002). As shown in Figure 1b, p21 protein levels in A2780 cells increased considerably upon exposure to the proteasome inhibitor MG-132.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, most TGCTs lack p21 protein expression (Guillou et al, 1996;Bartkova et al, 2000;Datta et al, 2001). Several studies have shown that p21 is not only an important mediator of p53-induced cell cycle arrest (El-Deiry et al, 1993 but also of apoptosis suppression following DNA-damaging agents exposure (Gorospe et al, 1997;Gervais et al, 1998;Levkau et al, 1998;Asada et al, 1999;Zhang et al, 1999). The reduced p21 expression in TGCT cells may thus not only result in a less efficient inhibition of cell cycle progression but also fail to prevent rapid apoptosis induction upon DNA damage.…”
Section: Introductionmentioning
confidence: 99%
“…54 The roles of both families in G 1 phase arrest and induction of differentiation and apoptosis have been thoroughly studied. [55][56][57][58] In SCC cells, the CIP1/KIP1 family appears to play a more important role than the INK4 family because p21 waf1/cip1 is strongly expressed but p16 INK4a is weakly expressed. 59,60 In the present study, p16 INK4a expression was not increased in the Mn-SOD antisense-transfected SCC cells, while p21 waf1/cip1 expression was increased and coordinated with the upregulation of Bax and downregulation of Bcl-2 expression.…”
Section: Discussionmentioning
confidence: 99%